Shifting of Batik Clothing Style as Response to Fashion Trends in Indonesia - Tyar Ratuannisa; Imam Santosa; Kahfiati Kahdar; Achmad Syarief (Mudra Jurnal Seni Budaya, 2020)
Fashion style refers to the way of wearing certain categories of clothing related to the concept of taste that refers to a person’s preferences or tendencies towards a particular style. In Indonesia, clothing does not only function as a body covering but also as a person’s style. One way is to use traditional cloth is by wearing batik.Batik clothing, which initially took the form of non -sewn cloth, such as a long cloth, became a sewn cloth like a sarong that functions as a subordinate, evolved with the changing fashion trends prevailing in Indonesia. At the beginning of the development of batik in Indonesia, in the 18th century, batik as a women’s main clothing was limited to the form of kain panjang and sarong. However, in the following century, the use of batik clothing became increasingly diverse as material for dresses, tunics, and blouses.This research uses a historical approach in observing batik fashion by utilizing documentation of fashion magazines and women’s magazines in Indonesia. The change and diversity of batik clothing in Indonesian women’s clothing styles are influenced by changes and developments in the role of Indonesian women themselves, ranging from those that are only doing domestic activities, but also going to school, and working in the public. However, fashion trend factors are also a parameter of change in batik clothing, which result in adaptive and flexible batik clothing.